GENETIC DIVERSITY OF CASSAVA (Manihot esculenta Crantz), (EUPHORBIACEAE) GROWN IN THREE AGROCLIMATIC ZONES OF CENTRAL AFRICAN REPUBLIC - Zinga, Innocent; E, Kosh Komba; F, Duval M; S, Akpavi; A, Atato; P, Yandia; K, Batawila; S, Semballa; K, Akpagana (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Cassava (Manihot esculenta Krants) introduced in the Central African Republic (CAR) in the 1850s, is now the staple food of the population. It does not know the genetic diversity of cultivated accessions in peasant communities. To assess this diversity, microsatellite technique was used on the 179 accessions identified. 137 alleles were amplified with an average of 5.95 alleles at the 23 loci. Analysis of genetic diversity within varieties across five villages showed that 46 accessions of 49 have a genotypic homogeneity is 93.87%. Only accessions "Tokonenanga" (Ndanga) "Touguenlag" (Soungbe) and "Sereka" (Karama) are each represented by two different genotypes.